The Effect of Question Answer Relationship (QAR) Strategy in Enhancing Students’ Reading Comprehension - Zelvia Liska Afriani; Meita Anggraini; Riswanto Riswanto (Journal of English Education and Teaching, 2020)
The aim of this study was to find out the effect of Question Answer Relationship (QAR) strategy in increasing students’ reading comprehension. The method used in this research was quasi experimental design. The sample of this study was 30 students of X hospitality accommodation, selected by using the purposive sampling method. They were divided into two classes, 15 students as experimental class who were taught using Question Answer Relationship Strategy and 15 others as control classes who were not taught by using QAR Strategy. In collecting data, the researchers provide tests twice, namely pre-test and post-test. Before conducting the post-test the, researcher gave three treatments in the experimental and control classes with different teaching. The instrument used in this study was 20 multiple choice questions about narrative texts that had been declared valid. The data obtained from pre-test and post-test were analyzed by using t-test. The result of the t-table was 1.76 and the result of the t-test was 2.690. It revealed that the t-test is bigger than the t-table (2.690> 1.76). Therefore, the null hypothesis (Ho) is rejected and the alternative hypothesis (Ha) is accepted. In brief, QAR Relationship Strategy can be one of effective ways in teaching reading for tenth grade students of SMK Yadika Model Lubuk Linggau.